KONTRIBUSI KELINCAHAN DAN DAYA TAHAN (VO2MAX) DENGAN KETERAMPILAN MENGGIRING BOLA PADA TIM SEPAKBOLA PUTRA SMK MUHAMMADIYAH 2 PEKANBARU - M. Noor Aldiansyah; Saripin '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Agility and endurance is a skill which is football player must have. This study aims to find out how big the contribution of agility and endurance with dribbling skills of SMK Muhamadiyah 2 Pekanbarufootball team. The sample in this study amounted to 20 peoples with sampling technique of total sampling. Instrument agility with dodging run, endurance with bleep test, and dribble. At the time of analysis, there are some problems that occur such as at the time of dribbling, the ball loose control on the mastery, and the difficulty to break through the opponent's defense. Based on the results of the study, the data shows that there are contribution of agility, endurance, or combined both (agility and endurance) to the students' skills in dribbling. Percentage of agility, endurance, and agility and endurance of SMK. Muhamadiyah 2 Pekanbaru football team, each of which amounted to 45.74%, 28.30%, And 54.87%.Keywords: Agility, endurance, dribbling